Cancer and Health Inequalities - Donna Wakefield; Clare Bambra (British Journal of Cancer, 2026)
Abstract Cancer is subject to stark inequalities, with mortality rates 60% higher in the most deprived parts of the UK. Most research has focused on the role of behavioural risk factors or access to health care services. Insufficient attention has been paid to the influence of socio-economic factors across the whole cancer continuum. This essay argues that to reduce cancer inequalities and improve patient experience and clinical outcomes, we need to look more widely at inequalities in: (1) the risk of developing cancer; (2) the effectiveness of prevention, detection and diagnosis; (3) treatment; (4) survivorship, and (5) access to palliative care. We argue that a stronger awareness and understanding of the influence of the wider social, economic and cultural context of health can enable clinicians to improve the delivery of more equitable cancer care. We conclude by recommending ways forward to improve the cancer continuum for everyone .